PROFIL PEDAGANG KAKI LIMA PADA MASYARAKAT NELAYAN DI KOTA REMBANG: STUDI PEDAGANG NASI BUNGKUS - Sri Mulyani Wahono (STIE Pelita Nusantara Semarang, 2007)
The contribution given by sectors of trade especially pedagang kaki lima (packed meal sellers) in economic activity and citizens’ prosperous (especially citizens’ from weak economic segment) in Rembang, ca be found within the coastal area society, that is fishermen society. The fact shows that Local Government. With the considerations to nature condition and its potentials, the maintenance of packed meal sellers’ activity, has to be the environmental concepts. Therefore,the existence of packed meal sellers might be grown to be a productive and environmentally – concepted sector.